Pengaruh rasio keuangan alam mendeteksi kecurangan laporan keuangan: Perusahaan consumer non-cylicals di Bursa Efek Indonesia tahun 2018-2021 - Putri, Narifa Alya; Nuryatno, Muhammad (LPMP Imperium, 2023)
The study aims to analyze Leverage (debt to equity & debt to asset), Profitability (gross profit margin), Asset Composition, Liquidity (Current Ratio), and Capital Turnover affect Financial Statement Fraud. The population used by non-cylical consumer companies listed from the Indonesia Stock Exchange (IDX) in 2018-2021. The sampling technique of this study is by purposive sampling. This study used multiple regression and IBM SPSS. Secondary data includes annual financial statements. The results of the writing concluded that debt to equity, debt to asset, gross profit margin, Asset Composition did not have a significant effect on financial statement fraud. Current Ratio and Capital Turnover have a significant negative effect on financial statement fraud.